The development of higher order thinking skills (HOTS) questions for static fluid concept. (February 2020) - Rizki, M; Sulastri,; Mursal,
Abstract: The achievements of Indonesian students at TIMMS are still categorized low. One of the reasons is that students are poorly trained in solving HOTS problems. The observations showed that questions used in the 2017/2018 odd semester exam in high schools in Banda Aceh were still categorized as LOTS, so giving HOTS questions has become a necessity. The purpose of this study was to develop and analyze HOTS questions on static fluid materials. The method used was research and development (R&D) with the ADDIE model. The number of samples was 66 students who were selected using a random sampling technique. The data were collected through questionnaires and written tests. The average percentage of expert validation was 97.98% which indicated a very decent category. The quality of the HOTS question test obtained 16 (20%) valid items and 4 (20%) invalid items. The reliability was 0.878 which indicated a very high category. The test item difficulty index consisted of 6 difficult items, 9 moderate items and 5 easy items. The confounders as much as 92.25% worked well and 8.75% did not work. It can be concluded that the questions from the results of this development can be used to train students HOTS.